JunB Is Critical for Survival of T Helper Cells - Hsieh, Tsunghan; Sasaki, Daiki; Taira, Naoyuki; Chien, Hsiaochiao; Sarkar, Shukla; Seto, Yu; Miyagi, Mio; Ishikawa, Hiroki (Frontiers in Immunology, 2022)
Clonal expansion and differentiation of various T helper subsets, such as Th1, Th2, and Th17 cells, depend on a complex of transcription factors, IRF4 and a BATF-containing AP-1 heterodimer. A major BATF heterodimeric partner, JunB, regulates Th17 differentiation, but the role of JunB in other T helper subsets is not well understood. Here we demonstrate that JunB is required for clonal expansion of Th1, Th2 and Th17 cells. In mice immunized with lipopolysaccharide (LPS), papain, or complete Freund’s adjuvant (CFA), which induce predominantly Th1, Th2 and Th17 cells, respectively, accumulation of antigen-primed, Junb-deficient CD4+ T cells is significantly impaired. TCR-stimulated Junb-deficient CD4+ T cells are more sensitive to apoptosis, although they showed largely normal proliferation and cellular metabolism. JunB directly inhibits expression of genes involved in apoptosis, including Bcl2l11 (encoding Bim), by promoting IRF4 DNA binding at the gene locus. Taken together, JunB serves a critical function in clonal expansion of diverse T helper cells by inhibiting their apoptosis.